Review on equipment configuration and operation process optimization of hydrogen refueling station. (15th January 2022) - Tian, Zheng; Lv, Hong; Zhou, Wei; Zhang, Cunman; He, Pengfei
Abstract: The construction of hydrogenation infrastructure is important to promote the large-scale development of hydrogen energy industry. The technical performance of hydrogen refueling station (HRS) largely determines the refueling efficiency and cost of hydrogen fuel cell vehicles. This paper systematically lists the hydrogen refueling process and the key equipment applicable in the HRS. It comprehensively reviews the key equipment configuration from the hydrogen supply, compression, storage and refueling of the HRS. On the basis of the parameter selection and quantity configuration method, the process optimization technology related to the equipment utilization efficiency and construction cost was quantitatively evaluated. Besides, the existing problems and prospects are put forward, which lays the foundation for further research on the technical economy of HRSs. Highlights: The key equipment and process flow of the HRSs are discussed. The hydrogen supply system configuration is analyzed from three hydrogen sources. The configuration and optimization of hydrogen storage vessels are presented. The compressor configuration matched with hydrogen storage are described. The empirical and queuing method of hydrogen dispenser configuration are explained.